2011
DOI: 10.1021/nn201199b
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Conductance of Pyridine-Terminated Dithienylethene Switch Molecules

Abstract: SynthesisFig. S1. Steps in the synthesis protocols, described in detail in the Methods section of the main text. Additional Experimental DetailsAs verification of the ability of our apparatus to produce results consistent with those published previously, we measured several molecules studied by Venkataraman and collaborators. In Fig. S2 we show results for four diaminoalkanes (with 3, 4, 10, and 12 carbons). The conductance values we obtain are in good agreement with the previous measurements.1 A linear fit to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 47 publications
3
90
0
Order By: Relevance
“…The transmission for 1on t ( T ≈ 7 × 10 −4 ) is higher than for 2on t ( T ≈ 5 × 10 −5 to 2 × 10 − 4 ). Still, both values are higher than those observed for DAEs with shorter side‐arms and lower switching efficiency 15, 27. Apparently, decoupling of the excited states of the switching core by the OPE wires does not result in a reduced conductance.…”
Section: Discussionmentioning
confidence: 75%
“…The transmission for 1on t ( T ≈ 7 × 10 −4 ) is higher than for 2on t ( T ≈ 5 × 10 −5 to 2 × 10 − 4 ). Still, both values are higher than those observed for DAEs with shorter side‐arms and lower switching efficiency 15, 27. Apparently, decoupling of the excited states of the switching core by the OPE wires does not result in a reduced conductance.…”
Section: Discussionmentioning
confidence: 75%
“…Ralph et al reported a singlemolecule switch with pyridine-terminated dithienylethene with conducting closed configuration and nonconducting open configuration. 411 The pyridine groups were used to link the molecules to gold electrodes to achieve relatively well-defined molecular contacts and stable conductance.…”
Section: Nanomechanical Molecular Switchesmentioning
confidence: 99%
“…As a result, many electro-active properties, such as rectification78, negative differential resistance910 and Coulomb blockade11, have been uncovered, indicative of their promising applications in functional electronic devices. Additionally, external stimuli, such as light1213141516, mechanical force1718, magnetic field1920, electrical field212223 and electrochemical potential2425262728, were introduced to modulate the molecular conductivity and thus to tune the properties of functional molecular devices, thereby significantly driving their development. As attested by the giant magnetoresistance effect2930 and photoelectric cooperation3132, a better synergy between such external stimuli and corresponding fabrication of multi-addressable MTJs may further efficiently advance the field of molecular electronics.…”
mentioning
confidence: 99%
“…In addition to this photochromic property, we previously showed that such a ruthenium/DTE association can also perform electrochemical cyclization of the DTE unit in solution at low potential40, in contrast to organic systems4950. Therefore, since it has been successfully demonstrated that molecular conductance can be respectively tuned by light irradiation121314151644 or electrochemical potential2425262728, we were strongly motivated in the association of these two stimuli in a single electronic device to achieve orthogonally modulated MTJs.…”
mentioning
confidence: 99%